63.2k views
2 votes
Which equation is equivalent to

y-2 = -5(x + 6)?

Fy= -5x + 8
Gy= -5x + 3
Hy= -5x - 28
J y= 5x - 32

1 Answer

1 vote

Hey there! :)

We are given the equation:


\displaystyle \large{y - 2 = - 5(x + 6)}

First, we have to isolate y-term; add -2 both sides.


\displaystyle \large{y - 2 + 2= - 5(x + 6) + 2} \\ \displaystyle \large{y = - 5(x + 6) + 2}

Then we simplify the expression; distribute -5 in the x+6.


\displaystyle \large{y = - 5x - 30 + 2}

Evaluate:


\displaystyle \large{y = - 5x - 28}

Therefore, y = -5x-28 is equivalent to y-2=-5(x+6)

User ROHIT PARMAR
by
5.2k points